Hunger Pains : Life inside Foodbank Britain - Garthwaite, Kayleigh (Book collections on Project MUSE., 2016)
We know the statistics, but what does it feel like to be forced to turn to foodbanks for help? What does it take to get emergency food, and what's in the food parcel? This is a powerful insight into the harsh reality of foodbank use from the inside.